Bioluminescence Imaging of Vascular Endothelial Growth Factor Promoter Activity in Murine Mammary Tumorigenesis - Shannon L. Faley; Keiko Takahashi; Cornelia E. Crooke; Joshua T. Beckham; Takuya Tomemori; Scott B. Shappell; E. Duco Jansen; Takamune Takahashi (Molecular Imaging)
Vascular endothelial growth factor (VEGF) is a major inducer of angiogenesis. We generated a transgenic reporter mouse, VEGF-GL, in which an enhanced green fluorescent protein-luciferase fusion protein is expressed under the control of a human VEGF-A promoter. The VEGF-GL mouse exhibited intense bioluminescence throughout the body at 1 week of age. The signals rapidly declined to a relatively low level as the mice grew. The adult VEGF-GL mouse showed restricted bioluminescence to the areas undergoing wound healing. In contrast, the VEGF-GL mice, which were crossed with mouse mammary tumor virus-polyoma virus middle T antigen transgenic mammary tumor mice, exhibited prominent bioluminescence in the tumors, correlating with VEGF transcription. Tumor bioluminescence was observed in the bigenic mice as early as 8 weeks, before tumors were palpable, and the signals increased with tumor growth. In conclusion, the VEGF-GL mouse permits longitudinal and quantitative assessment of VEGF promoter activity in vivo. The model should facilitate understanding of the molecular controls and pathways that regulate VEGF transcription in vivo.